Okruchy. O książkach i strawie - Barakońska, Liliana (Er(r)go. Teoria - Literatura - Kultura, 2009)
Liliana Barakonska Of Books and Foods Summary The article is an attempt to analyse the functioning of the consumption metaphor in the context of Robert Burton's work The Anatomy of Melancholy (1621) with special attention paid to the link between the writing activity and the process of digestion. Thus it explores the ways in which Burton reads Seneca' s project of constructing the self out of hypomnemata, selected fragments of various texts to be digested and incorporated to model a new personality; a project evoked by Erasmus who advocates digestion of classical authors in order to produce a new and individual style in writing. Establishing an analogy between the space of his book and the space of an inn, Burton establishes an analogy between words and foods, thus endeavouring to refer his work to the oral literary tradition. Writing his discourse in the Jacobean context, however, the feast Burton presents the reader with is, as he puts it, exremental: what he has at his disposal as a writer are remnants and leftovers. Hence, to study the implications of Burton's vision, it is necessary to relate it to the prevalent presentation of food imagery. The article is thus a reading of the changes in the representation of food between the Elizabethan and Jacobean periods and situates the discourse of melancholy in the digestive and excretory metaphor of the time.